Ranking academic performance using fuzzy vikor: A case of secondary schools at Perlis / Siti Nor Nadrah Muhamad ... [et al.] - Muhamad, Siti Nor Nadrah; Abd Halim, Rasyidah; Wan Shahidan, Wan Nurshazelin; Jusoh @ Hussain, Nordianah; Sarkam, Saida Farhanah (UiTM Cawangan Perlis, 2018)
Ranking is the process of structuring alternatives in order of priority. It is based on the criteria determined for each alternative involved. In this study, the researcher analyzed the percentage of candidates who scored in the 2016 Malaysia secondary school national examination, Sijil Pelajaran Malaysia (SPM), in the state of Perlis. The schools represent an alternative, while the examination subjects as the criterion. The study used fuzzy VIKOR method to determine the priority rank for the performance of five schools. Fuzzy VIKOR method evaluates the criteria and compose composite index of each alternative for the purpose of arranging them in order of preference alternatives. The result showed that fuzzy VIKOR method is able to rank the data more fair and accurate than other conventional methods such as TOPSIS (Technique for Order Preference by Similarity to an Ideal Solution) and PROMETHEE (Preference Ranking Organization METHod for Enrichment Evaluations). By using the proposed approach, the ambiguity involved in the evaluation data can be effectively represented and processed to assure a more effective evaluation process. The accurate ranking of schools might benefit the Education Ministry at the district level as more resources could be provided to the least performed school.